Estudio comparativo del delito de cohecho activo transnacional en el derecho penal peruano y español - Armendariz Ochoa, Luis Fernando (Pontificia Universidad Católica del Perú, 2025)
This study critically and comparatively examines the characteristic aspects of the crime of active transnational bribery, considering its treatment in the regulations of Peru and Spain. In this context, from a criminological and historical approach to the fight against global corruption, but with special emphasis on Spanish criminal legal doctrine, we seek to contribute to its analysis and improvement. With this purpose, various proposals for regulatory reform will be presented for the current classification of active transnational bribery,among which the incorporation of a legal definition of the term “foreign public official or member of an international body” and the classification of a modalityof active transnational bribery, not exclusively linked to economic objectives, stand out. Finally, the criminal responsibility of legal entities in relation to the crime of international bribery will be addressed, emphasizing the essential requirements for correct accusation and, as a priority, the justification of their criminal sanction.

Este estudio examina de manera crítica y comparativa los aspectos característicos del delito de cohecho (soborno) transnacional activo y considera su tratamiento en las normativas de Perú y España. En este contexto, a partir de un enfoque criminológico e histórico sobre la lucha contra la corrupción global, pero con especial énfasis en la doctrina jurídico penal española, se busca contribuir a su análisis y mejora. Con este propósito, se presentarán diversas propuestas de reforma normativa para la actual tipificación del soborno transnacional activo, entre las cuales sobresalen la incorporación de una definición legal del término “funcionario público extranjero o integrante de un órgano internacional” y la tipificación de una modalidad de cohecho internacional no vinculada exclusivamente a objetivos económicos. Por último, se abordará la responsabilidad penal de las personas jurídicas en relación con el delito de soborno internacional y resaltaremos los requisitos esenciales para una correcta imputación y, de manera prioritaria, en la justificación de su sanción penal.
Comparative Study of the Crime of Transnational Bribery in Peruvian and Spanish Criminal Law
Keywords: Transnational corruption; Active international bribery; OECD; Criminal law; Comparative law; Corrupción transnacional; Cohecho activo internacional; OCDE; Derecho penal; Derecho comparado; https://purl.org/pe-repo/ocde/ford#5.05.01